Multiple Attribute Group Decision-Making Methods Under Hesitant Fuzzy Linguistic Environment - Liu Xiaodi; Zhu Jianjun; Zhang Shitao; Liu Guodong (Journal of Intelligent Systems, 2017)
The aim of this paper is to develop some aggregation operators for multiple-attribute group decision making (MAGDM) with hesitant fuzzy linguistic information. First, the relationship between uncertain linguistic variable and hesitant fuzzy linguistic term set (HFLTS) is discussed. Some operations and aggregation operators for HFLTSs are developed. Second, based on the hesitant fuzzy linguistic weighted arithmetic averaging operator and the hesitant fuzzy linguistic hybrid averaging operator, an approach to MAGDM problem with hesitant fuzzy linguistic information is proposed. Finally, a practical application of the developed approach to supplier selection in a supply chain and a comparative analysis with other methods are presented.